(untitled) (Proceedings of the International Conference on Education, 2023)
The data on cybersexual harrashment in tertiary institutions is increasing along with the awareness and courage of the victims and the community to "speak out" regarding cases of sexual harrashment, including cybersexual cases. Based on data from the report of the Indonesian Women’s National Commission (Komnas) from 2015 to 2020, the number of cases of sexual harrashment in educational institutions was quite high, at around 27%, with incidents in higher education institutions ranking highest . The Ministry of Education and Culture has also issued a ministerial regulation regarding the prevention and handling of sexual harrashment (PPKS) to minimize cases of sexual harrashment that occur in tertiary institutions because this can have a negative impact on psychological aspects, especially victims of mental health . This study aims to look at the impact of cybersexual harrashment to mental health people in the university environment ,. Respondents in this study were the academic community at tertiary institution "X" totaling 425 respondents using the convenient sampling technique. Data analysis using regression analysis techniques. This research has gone through a research ethics test. The results of this study there is an effect of cybersexual harrashment to mental health, that indicate the higher the cybersexual harrashment experienced, the lower the mental health condition. The effect contribution is 8,5%. The person in the academic community in university who have experience as a victim of cybersexual are given protection and recovery from universities, academics and families and synergizes with government in efforts to prevent and deal with cybersexual harrashment so that there are no other victims in the higher university.